A Systematic Review of Anxiety and Depression in Children and Adolescents: Risk Factors, Impacts, and Interventions - Dame Triulina Hutasoit (Universitas Pahlawan Tuanku Tambusai, 2025)
Anxiety and depression are the most prevalent mental health disorders among children and adolescents, with a globally rising trend. This study adopts a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines to examine the risk factors, psychosocial impacts, and interventions associated with these disorders in individuals aged 0–18 years. Literature was sourced from the Scopus database using the keywords “Anxiety and Depression” and “Children and Adolescents,” limited to publications from 2015 to 2025. From an initial pool of 237 articles, 14 met the inclusion criteria, which required a focus on the child-adolescent population, discussion of anxiety and/or depression, availability of full-text and abstract, and publication in reputable journals (Q1–Q4). The findings indicate that anxiety and depression frequently co-occur, often accompanied by symptoms such as loneliness and irritability. Major risk factors include childhood trauma, physical and emotional abuse, poverty, neurodivergent conditions, and the interplay of genetic and environmental influences. These disorders impact emotional, social, and academic functioning, particularly among vulnerable groups. Effective interventions include structured physical activity, digital cognitive behavioral therapy (CBT), and social support. The study underscores the importance of multidisciplinary and cross-sectoral approaches and recommends early detection, training for educators and parents, and the integration of child mental health policies.